2015
DOI: 10.3109/01443615.2015.1009878
|View full text |Cite
|
Sign up to set email alerts
|

Patient compliance with postnatal thromboprophylaxis: An observational study

Abstract: Prescription of postnatal thromboprophylaxis has increased with the Royal College of Obstetricians and Gynaecologists and the National Institute for Health and Care Excellence guidance. Our study of postnatal women meeting the criteria for thromboprophylaxis aimed to ascertain compliance with low-molecular-weight heparin and barriers to completion of a full course. Women were recruited from the antenatal clinic or postnatal wards. Those who agreed were contacted by telephone 14 days after delivery and asked ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 5 publications
2
38
0
Order By: Relevance
“…We found a relatively high self-reported adherence rate to pharmacological TP (82.4%). This is in line with previously reported studies in this population group [11][12] and suggests that when women are prescribed parenteral pharmacological TP, largely, they will adhere. In Patel and colleagues study, postnatal adherence to enoxaparin was reported at 93%, where the same women had also been prescribed antenatal TP [11].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We found a relatively high self-reported adherence rate to pharmacological TP (82.4%). This is in line with previously reported studies in this population group [11][12] and suggests that when women are prescribed parenteral pharmacological TP, largely, they will adhere. In Patel and colleagues study, postnatal adherence to enoxaparin was reported at 93%, where the same women had also been prescribed antenatal TP [11].…”
Section: Discussionsupporting
confidence: 92%
“…We found no difference between perceived necessities and concerns in relation to mode of delivery or ethnicity. Horden and colleagues have also reported that women are highly accepting of postnatal TP [12]. In their study, 94.5% of women questioned indicated that they would accept TP in a future pregnancy.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations